Transcriptomics assisted by metabolomics analysis provides insights into regulation mechanisms during carcinogenic process in a hydrodynamically transfected liver cancer model - Qi Zhang; Yongfeng Li; Xiaojing Cheng; Zhouxiang Liao; Sha Wen; Xuejing Huang; Zhenyu Song; Min He; Lichao Yang (Cancer Cell International)
Abstract Background Hepatocellular carcinoma (HCC) ranks among the most prevalent malignancies with a substantial mortality rate, and its pathogenesis is relatively complex. Animal models provide valuable tools for exploring the causes and mechanisms of malignancy. This study uses a novel hydrodynamic transfection mouse model to investigate the changes in key genes and metabolites during the development of HCC. By combining metabolomics-assisted transcriptomics assay, this research seeks to provide new insights into HCC development. Methods A mouse model of HCC was established using hydrodynamic transfection coupled with the SB11 transposon system and the CRISPR-Cas9 system. C57BL/6J mice were used as experimental animals, with mice arbitrarily split into the control and experimental groups. The experimental group of mice underwent hydrodynamic transfection using mixed recombination carcinogenic plasmids that knocked out the tumor suppressor genes Pten and P53, while overexpressing the oncogenes β-catenin and c-Met. In contrast, the control group of mice was transfected with corresponding empty vectors. All mice were monitored for weight, activity, and blood routine examinations during the modeling phase. All mice were sacrificed upon completion of the modeling phase, and their liver specimens were harvested for pathological evaluations and metabolomics-assisted transcriptomics investigation. Results In contrast to the control group, the experimental group mice exhibited notably smaller weight gain (P < 0.01) and markedly elevated serum ALT and AST levels (P < 0.001). At the end of the modeling period, visible white nodules appeared in the liver; hematoxylin and eosin (H&E) staining, immunohistochemistry, and electron microscopy revealed pathological features of HCC in the experimental group. Transcriptome analysis ascertained 2757 differentially expressed genes (DEGs) between HCC tissues and control liver tissues, with 2273 elevated and 484 diminished genes. KEGG pathway evaluation indicated substantial clustering of DEGs in cell cycle signaling pathways. Metabolome analysis showed the enrichment of differential metabolites in pathways related to ascorbate and alternate metabolism, choline metabolism in cancer, and glycerophospholipid metabolism. Notably, we observed significant differences in HCC progression between male and female mice after modeling, with female mice showing a higher incidence of HCC, greater liver-to-body weight ratios, and larger tumors than males. Transcriptome analysis and subsequent qRT-PCR demonstrated a significant downregulation of several glutathione transferase family genes (Gata1, Gata2, Gstp1, Mgst1) in the liver tissues of female mice versus males in the experimental group. Liver metabolome analysis revealed that female mice in the experimental group had 57 metabolites that differed from those of male mice, with 24 metabolites being upregulated and 33 downregulated. In particular, female mice exhibited markedly higher levels of glutamate, alanine, L-pyroglutamic acid, and glycerophospholipids (P < 0.05), while their pyridoxine levels were notably lower (P < 0.05) compared to male mice in the liver. Conclusions In a hydrodynamic transfection-based mouse model of HCC, female mice showed higher tumor incidence, faster tumor growth, and more severe disease compared to male mice. This sex-based difference may be associated with lower hepatic expression of glutathione S-transferases (GSTs) in females. Targeting GST expression or activity may offer a potential strategy for sex-informed approaches to HCC prevention and therapy.